Farmers' knowledge of Q fever and prevention approaches in New South Wales. (15th June 2017) - Lower, Tony; Corben, Paul; Massey, Peter; Depczynski, Julie; Brown, Tony; Stanley, Priscilla; Osbourn, Margaret; Durrheim, David
Abstract: Objective: To identify what New South Wales (NSW) farmers know about Q fever to inform preventive approaches. Design: Thematic analysis of qualitative data gathered through semi‐structured individual interviews, focus groups and a community meeting. Setting: Rural communities in NSW, Australia. Participants: A total of 25 farmers participated in individual interviews ( n = 4) or three focus groups, each with seven participants ( n = 21). A further 27 persons, were involved in a community meeting. Main outcome measures: Themes derived from the interviews, focus groups and community meeting. Results: Knowledge variations regarding Q fever risk and transmission highlight a need for improved risk communication. Vaccination was viewed as the preferred prevention approach; barriers were raised including time, costs, access to screening/vaccination and General Practitioner (GP) knowledge about Q fever. Local vaccination initiatives were supported. Conclusions: Strengthening existing GP knowledge and services leading to expanded provision of screening/vaccination could improve the coverage of Q fever vaccine in endemic NSW farming and rural communities.